2014
DOI: 10.1093/ehjci/jeu183
|View full text |Cite
|
Sign up to set email alerts
|

T1 mapping in dilated cardiomyopathy with cardiac magnetic resonance: quantification of diffuse myocardial fibrosis and comparison with endomyocardial biopsy

Abstract: ECV measurement with CMR reflects myocardial collagen content in DCM. Therefore, CMR-based assessment of ECV may have the potential to serve as a non-invasive tool for the quantification of diffuse MF in order to monitor therapy response and aid risk stratification in different stages of DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
146
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(156 citation statements)
references
References 36 publications
8
146
0
2
Order By: Relevance
“…Because of its ability to recognize subclinical diffuse myocardial involvement, as well as a measure of longitudinal changes of myocardial inflammation, T1 mapping seems promising for detecting subclinical pathophysiological changes, potentially allowing us to modify the course of disease. This is supported by histological data 45,51 on accumulation of diffuse fibrosis and the parallel relationships of T1 mapping with progressive ventricular remodeling and stiffness in DCM. 11,45,[83][84][85][86] Abnormal T1-mapping indices were also found in other common causes of DCM, including patients with cardiac amyloidosis, [87][88][89] diabetic cardiomyopathy, 34,90 and iron overload cardiomyopathies.…”
Section: T1 Mapping In Nonischemic Dilative Cardiomyopathysupporting
confidence: 55%
See 3 more Smart Citations
“…Because of its ability to recognize subclinical diffuse myocardial involvement, as well as a measure of longitudinal changes of myocardial inflammation, T1 mapping seems promising for detecting subclinical pathophysiological changes, potentially allowing us to modify the course of disease. This is supported by histological data 45,51 on accumulation of diffuse fibrosis and the parallel relationships of T1 mapping with progressive ventricular remodeling and stiffness in DCM. 11,45,[83][84][85][86] Abnormal T1-mapping indices were also found in other common causes of DCM, including patients with cardiac amyloidosis, [87][88][89] diabetic cardiomyopathy, 34,90 and iron overload cardiomyopathies.…”
Section: T1 Mapping In Nonischemic Dilative Cardiomyopathysupporting
confidence: 55%
“…More importantly, they revealed abnormal T1 values in the remote, noninfarcted myocardium and a significant relationship with histologically determined collagen volume fraction, allowing an insight into the state of pathological remodeling in what was commonly considered as a normal reference. Later studies reiterated this relationship in patients with HF, [42][43][44][45] severe aortic stenosis, [46][47][48][49][50] and HCM 46 ( Table 3). Although these studies reported significant relationship with collagen volume fraction for all T1 indices, there is a considerable variation in the strengths of observed relationships.…”
Section: T1-mapping Indices: Initial Experience and Histological Corrmentioning
confidence: 93%
See 2 more Smart Citations
“…Several studies have explored tissue validation of T1 mapping [1][2][3]. Currently, T1 relaxation time and calculated extracellular volume fraction (ECV) are accepted as reliable markers of the degree of diffuse interstitial fibrosis [4].…”
Section: Introductionmentioning
confidence: 99%